A Scoping Review of the Use of Social and Behavioral Change in Acute Care Antimicrobial Stewardship Initiatives. (February 2022) - Hemenway, Alice N.; DuBois, David L.
Purpose: Antimicrobial stewardship (AS) initiatives are implemented with a goal of reducing antimicrobial resistance. It is unknown exactly how many acute care AS initiatives have since been based on social and behavioral theory. The purpose of this scoping review is to provide an updated review of theory-informed acute care AS initiatives in the published literature, including how social and behavioral theories have been used in the described interventions.Methods: PubMed, EMBASE, CINAHL, PsycINFO, and ProQuest Dissertations were searched using a combination of AS, acute care, and social and behavioral theory search terms from April 2011 to November 2019. Using both an initial review of titles and abstracts and a second review of full text, a total of 4 articles were identified after a review of 2014 records. Each article was coded using a guide that abstracted details of study methods, the AS intervention, and use of theory based on a validated theory coding scheme.Results: The interventions included combinations of decision-making tools, provider education, and prospective audit and feedback. Two studies included an evaluation of the described initiative, with findings indicating improvement in antimicrobial use. All interventions utilized theory in developing AS interventions. However, gaps were evident in the use of theory in the evaluations, including inconsistent measurement of theory constructs and lack of testing of the theory.Conclusion: AS interventions are frequently published; however, theory-based acute care AS interventions are not commonly described. More consistent and comprehensive utilization of social and behavioral theories may enhance effectiveness of AS programs.